Connections of the Human Orbitofrontal Cortex and Inferior Frontal Gyrus. (17th June 2020) - Heather Hsu, Chih-Chin; Rolls, Edmund T; Huang, Chu-Chung; Chong, Shin Tai; Zac Lo, Chun-Yi; Feng, Jianfeng; Lin, Ching-Po
Abstract: The direct connections of the orbitofrontal cortex (OFC) were traced with diffusion tractography imaging and statistical analysis in 50 humans, to help understand better its roles in emotion and its disorders. The medial OFC and ventromedial prefrontal cortex have direct connections with the pregenual and subgenual parts of the anterior cingulate cortex; all of which are reward-related areas. The lateral OFC (OFClat) and its closely connected right inferior frontal gyrus (rIFG) have direct connections with the supracallosal anterior cingulate cortex; all of which are punishment or nonreward-related areas. The OFClat and rIFG also have direct connections with the right supramarginal gyrus and inferior parietal cortex, and with some premotor cortical areas, which may provide outputs for the OFClat and rIFG. Another key finding is that the ventromedial prefrontal cortex shares with the medial OFC especially strong outputs to the nucleus accumbens and olfactory tubercle, which comprise the ventral striatum, whereas the other regions have more widespread outputs to the striatum. Direct connections of the OFC and IFG were with especially the temporal pole part of the temporal lobe. The left IFG, which includes Broca's area, has direct connections with the left angular and supramarginal gyri.